Current Therapeutic Strategies for Obesity in the Pediatric Population: A Literature Review - Rokosz, Julia; Mazur, Krzysztof; Michałek, Sandra; Koczuk, Julianna; Sładek, Katarzyna; Trzepizur, Alicja; Spaczyńska-Kwiatkowska, Monika (Quality in Sport, 2026)
Background: Childhood obesity is a major public health problem in both developing and developed countries. It is a chronic, complex, and progressive disease influenced by multiple genetic, psychological, dietary, familial, environmental, and biological factors. It is associated with a wide range of short- and long-term multiorgan complications, many of which persist into adulthood, increasing the risk of chronic multimorbidity. Therefore, early prevention and appropriate treatment are essential. Aim: To review current therapeutic strategies for pediatric obesity, focusing on lifestyle and behavioral interventions, pharmacotherapy, and bariatric surgery, and to evaluate their effectiveness and clinical applicability. Materials and methods: A literature review was conducted using PubMed, the Cochrane Library, and Google Scholar, focusing mainly on studies published after 2020 addressing lifestyle, psychological, pharmacological, and surgical management of obesity in children and adolescents. Results: The therapeutic approach is holistic, based on sustainable lifestyle modification, including dietary changes, physical activity, reduced sedentary behavior, and family involvement. Cognitive-behavioral therapy is crucial in modifying maladaptive behaviors. Pharmacotherapy has expanded options, with GLP-1 receptor agonists (semaglutide, liraglutide) showing the greatest effectiveness, while orlistat, phentermine/topiramate, and setmelanotide may provide additional benefit. Bariatric surgery remains the most effective intervention for severe adolescent obesity, resulting in substantial and sustained weight loss. Conclusions: Management should be multidisciplinary, with individualized behavioral and psychological interventions as the foundation. Pharmacotherapy and bariatric surgery should be considered in selected patients with severe obesity or inadequate response to conservative treatment.